Vascular Dysfunction of COVID-19 Is Partially Reverted in the Long-Term. Issue 9 (29th March 2022) - Zanoli, Luca; Gaudio, Agostino; Mikhailidis, Dimitri P.; Katsiki, Niki; Castellino, Niccolò; Lo Cicero, Lorenzo; Geraci, Giulio; Sessa, Concetto; Fiorito, Letizia; Marino, Francesca; Antonietta Di Rosolini, Maria; Colaci, Michele; et al.
Abstract : Background: COVID-19 is characterized by severe inflammation during the acute phase and increased aortic stiffness in the early postacute phase. In other models, aortic stiffness is improved after the reduction of inflammation. We aimed to evaluate the mid- and long-term effects of COVID-19 on vascular and cardiac autonomic function. The primary outcome was aortic pulse wave velocity (aPWV). Methods: The cross-sectional Study-1 included 90 individuals with a history of COVID-19 and 180 matched controls. The longitudinal Study-2 included 41 patients with COVID-19 randomly selected from Study-1 who were followed-up for 27 weeks. Results: Study-1: Compared with controls, patients with COVID-19 had higher aPWV and brachial PWV 12 to 24 (but not 25–48) weeks after COVID-19 onset, and they had higher carotid Young's elastic modulus and lower distensibility 12 to 48 weeks after COVID-19 onset. In partial least squares structural equation modeling, the higher the hs-CRP (high-sensitivity C-reactive protein) at hospitalization was, the higher the aPWV 12 to 48 weeks from COVID-19 onset (path coefficient: 0.184; P =0.04). Moreover, aPWV (path coefficient: −0.186; P =0.003) decreased with time. Study-2: mean blood pressure and carotid intima-media thickness were comparable at the end of follow-up, whereas aPWV (−9%; P =0.01), incremental Young's elastic modulus (−17%; P =0.03), baroreflex sensitivity (+28%; P =0.049), heart rate variability triangular index (+15%; P =0.01), and subendocardial viability ratio (+12%; P =0.01×10 −4 ) were significantly improved. There was a trend toward improvement in brachial PWV (−6%; P =0.14) and carotid distensibility (+18%; P =0.05). Finally, at the end of follow-up (48 weeks after the onset of COVID-19) aPWV (+6%; P =0.04) remained significantly higher in patients with COVID-19 than in control subjects. Conclusions: COVID-19-related arterial stiffening involves several arterial tree portions and is partially resolved in the long-term.